A Estação: Considerações sobre a moda e seu léxico no século XIX no Brasil - Orsi, Vivian (2021)
Fashion, with its own language, establishes a group identity within the society and the period in which it is set. Moreover, it is a way of communication between the subject and the world around him. Fashion reflects the ongoing change of times in which its unfold and clothes are used as a social way of showing financial status and one’s role in society. It has the power to shape the mentality of a society using its own language. Therefore, the lexicon adopted within this universe is represented according to the particularities of a culture. This research proposes the study of the lexicon of fashion of the nineteenth century in Brazil, based on the lexical, etymological, neological and fashion studies, it is proposed to examine here some lexical items referring to clothes and accessories found in A Estação, published from 1879 to 1904. The results of the reflections allow the understanding of the search for the French model of language and social dynamics.